2016
DOI: 10.3989/scimar.04405.01a
|View full text |Cite
|
Sign up to set email alerts
|

Variability of planktonic and epiphytic vibrios in a coastal environment affected by <em>Ostreopsis</em> blooms

Abstract: Summary:Vibrios include several pathogenic bacteria that occur in aquatic environments. The presence of Vibrio has been assessed in many ecosystems by culture-based techniques. However, little is known on the contribution of vibrios in the sea, especially in areas subject to harmful algal blooms. A preliminary study in Sant Andreu de Llavaneres beach (NW Mediterranean) showed the presence of some Vibrio species during a recurrent bloom of the harmful benthic dinoflagellate Ostreopsis cf. ovata. In order to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 66 publications
2
6
0
2
Order By: Relevance
“…However, the absolute abundance of free-living Vibrio was higher than that of particle-associated Vibrio (Wilcoxon, P Ͻ 0.001), suggesting that more Vibrio populations remained free living rather than particle associated. This result was in line with the results of studies in several other regions, including the Baltic and Skagerrak Seas, as well as the Mediterranean (30,38). Based on these results, it can be assumed that although Vibrio has certain advantages over other bacteria when attached to particles, it is more inclined to live freely in the water column.…”
Section: Discussionsupporting
confidence: 89%
“…However, the absolute abundance of free-living Vibrio was higher than that of particle-associated Vibrio (Wilcoxon, P Ͻ 0.001), suggesting that more Vibrio populations remained free living rather than particle associated. This result was in line with the results of studies in several other regions, including the Baltic and Skagerrak Seas, as well as the Mediterranean (30,38). Based on these results, it can be assumed that although Vibrio has certain advantages over other bacteria when attached to particles, it is more inclined to live freely in the water column.…”
Section: Discussionsupporting
confidence: 89%
“…Another aspect to consider in the many facets of the toxicity attributed to Ostreopsis is the role of certain bacteria such as Vibrio, some of which are known to be responsible for wound infections in people swimming in marine waters. Bellés-Garulera et al (2016) found a positive correlation between Vibrio and Ostreopsis abundances in Sant Andreu de Llavaneres during a year cycle, and suggested a likely role of vibrios in injury infections suffered by beach users during the bloom. Future research should combine ecophysiological, toxicological and environmental (water and weather conditions) data and characterizations of the Ostreopsis blooms to unveil the important factors and mechanisms of the impact on human health.…”
Section: Discussionmentioning
confidence: 99%
“…The mucilage, rich in organic carbohydrates, appears also as biologically colonizable surface for the growth of some bacteria (Vanucci et al, 2016;Guidi et al, 2018) including Vibrio (Bellés-Garulera et al, 2016). This positive association for pathogenic bacteria increases the risk of health impacts posed by Ostreopsis to human populations.…”
Section: Importance Of the Mucus In Ostreopsis Biological Interactionsmentioning
confidence: 99%